Experimental and Numerical Studies of the Behavior and Energy Absorption of Foam-Filled Circular Tubes - P. Kaczyński; J. Karliński; M. Hawryluk (Archives of Metallurgy and Materials, 2020)
Following paper is focused on experimental and numerical studies of the behavior and energy absorption for both: quasi-static and dynamic axial crushing of thin-walled cylindrical tubes filled with foam. The experiments were conducted on single walled and double walled tubes. Unfilled profiles were compared with tubes filled with various density polyurethane foam. All experiments were done in order to possibility of the safety of the elements absorbing collision energy which can applied in car body. The dynamic nonlinear simulations were carried out by means of PAM-CRASH™ explicit code, which is dedicated calculation package to modelling of crush. Computational crushing force, plastic hinges locations and specimens post-crushed geometry found to be convergent with the real experiments results. Conducted experiments allowed to draw conclusion, that crashworthiness ability is directly proportional to foam density. The investigation of the experimental data revealed, that double walled tubes have greater energy absorbing ability. A proposed investigation enable to analyze and chosen of optimal parameters of these elements, which can use in automotive industry as an absorption energy components.